Identification of solid waste dumping site suitability of Kolkata Metropolitan Area using Fuzzy-AHP model - Swapan Paul; Sasanka Ghosh (Cleaner Logistics and Supply Chain)
The solid waste management (SWM) issue become a hot topic since the early 21st century, owing to the massive increase in global human population. This study centered on a most important urban center of Eastern India, the Kolkata Metropolitan Area (KMA) having a total population of nearly 14.72 million with an average per capita waste generation of about 383.89 gr/person/year, necessitating the identification of new landfill areas to handle such a massive waste load. Therefore, the current work tried to explore the most suitable new dumping sites for the KMA, taking into account 4 main (topographical and geomorphological, lithological, socio-economic, and hydrogeological) and 17 sub-parameters from aforementioned four main data groups, as suggested by the Central Pollution Control Board's guidelines. With this Fuzzy-Analytical Hierarchy Process (F-AHP) and weighted linear combination model was used to determine the weightage and ratings of the main and Sub-parameters. Result indicates that 40.59% of the study area is not suitable for dumping site construction, 29.34% is least suitable, 14.34% is moderate suitable and about 9.64% is under highly suitable zone. Furthermore, a site-based verification report reveals that over 15 spots, in different parts of the study area may have a potential for dumping of large volume of urban solid waste. Six of them might be the finest candidates for Kolkata, Howrah, and Chandannagar MC, the three municipal corporations of KMA. As such, considering all the topographical, environmental, social, hydrogeological components, the public sectors and city planners can follow and refer the result of this suitability analysis.